Deepfake Pornography as Qadzaf: Legal Status and Hudud Implications - Maulana, Faisal; Abbas, Sudirman (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The phenomenon of misuse of Artificial Intelligence (AI) technology, especially through deepfake techniques which are widely used in cases of pornographic abuse, has given rise to serious implications within the framework of Islamic law, especially related to the issue of defamation or qadzaf. This research specifically focuses on determining sanctions for perpetrators who create deepfake pornography, whether they deserve to be punished by Allah (hudud) or whether they are entitled to punishment determined by humans (ta’zir). By using normative legal research methods through a case study approach and literature study that relies on secondary data as well as primary and secondary legal materials, this study found that the creation of deepfake content containing pornographic elements has fulfilled the elements of qadzaf. Based on these findings, it is concluded that hudud punishment can be imposed on the perpetrators, showing that Islamic law has a strong response to contemporary problems such as technological advances, and is also expected to provide clear legal certainty for Muslims in facing ethical and moral challenges in the digital era.